Congestive heart failure and sepsis: a retrospective study of hospitalization outcomes from a rural hospital in Southwest Missouri. Issue 3 (30th September 2022) - Skovran, Alexandra; Hinke, Mason; Sloan, Shelly N. B.; Stahl, Greg; Johnson, Kerry; Goade, Scott; Arnce, Robert
Abstract: Background: Sepsis is the leading cause of death in hospitalized patients and significant effort has been made to facilitate early diagnosis and management. However, aggressive treatment can have negative effects, especially in patients with unstable volume status, such as those with congestive heart failure. Methods: We used electronic medical records to perform a retrospective study looking at hospital outcomes in patients from Southwest Missouri who were admitted with sepsis and had a comorbid diagnosis of hypertensive heart failure. Our primary outcome was in-hospital mortality. Results: We studied a total of 184 patients with the diagnosis of hypertensive heart failure with sepsis, and 348 patients with the diagnosis of sepsis that served as the baseline group. There was a total of 37 (20%) deaths in the hypertensive heart failure group and a total of 94 (27%) deaths in the baseline group. Conclusion: Our study showed no significant difference between the baseline group and those with hypertensive heart disease with heart failure.